The centralised hazardous gas detector using microcontroller / Ishak Annuar - Annuar, Ishak (2006)
Monitoring and controlling system are imperative to prevent human and environment from dangerous effect of various factors of pollution. Until now, air pollution has been analyzed with precision laboratory instrument which are time-consuming, expensive, and can seldom be used in real-time in the field. As such, nowadays many applications for measuring hazardous pollution a v~ry precision analysis .of the gas is not required, but only an alarm level detection and safety of human. In the meantime, most of lower cost sensor systems available in the market are portable and decentralized. A new approach to centralized hazardous gas detectors using a low cost microcontroller system is presented. All relative work pertaining to the completion of the centralized system which composes of the development of gas sensor circuits, slave microcontrollers , RS-232 to RS-485 converter, optional central station were described. The centralized system utilizes a master slave communication where one master device controls the others slaves devices. The main station for operation of the system is monitored using Graphical User Interface (GUI) developed based on QBasic environment. A stand-alone main station is also developed by PIC microcontroller as an alternative central station. The GUI based on Visual Basic software is also developed for upgrading the capability with a new communication computer port operating under window environment. The developed system has shown that the auto switching mode of transmission could be implemented via the PIC microcontroller and RS485 transceiver. The use of PIC microcontroller has made the proposed system to be small in size which meets the trend of current technology. The complete prototype system is developed and the performance is reported.